Evaluasi Pengolahan Limbah Sampah di TPS3R Pasar Cantik Ciputat - Tangerang Selatan - Hendra Candra; Melati Puspita Hakim; Siti Mulasih; Ramadani Pardian; Joned C. Saksana; M. Arief Noor; M. Ningrum Pratiwi; Miftah Febrianti’; Ahmad Khatimi; Nurul Aini; Firdaus Alahudi; Ririn Komariah (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2022)
The most important problem caused by humans is waste, because humans individually produce waste from the rest of the food and drinks they consume. This is certainly a common problem for the community and the government authorities. This PKM activity is a reservoir for community complaints and a mouthpiece to the government with using method counselling, discussion, visitation, and interview to administrators and communities around TPS3R in Pasar Cantik Ciputat which lasted for 3 (three) months and the team is 13 lecturers of STIE Ganesha Jakarta (7 lecturers of Management and 6 lecturers of Accounting). The result is that local community can understand the function of TPS3R more better. The lecturers through their writings or articles, will try to be an extension and verbal of the problems at TPS3R Pasar Cantik Ciputat. The solution obtained is for non-organic waste to be sorted and collected by the TPS3R team and then work with trash banks for recycling to get some funds to maintenance the tools then produce good compost and can be sold for the good price. The suggestion for academics and environmental activists then can collaborate with the local government to create sustainable programs and for TPS3R and communities around can propose to the local government to make a Trash Bank that integrates with TPS3R and then last thing is the government must care to the TPS3R and Trash Banks in their respective regions.